Function and evolutionary origin of unicellular camera-type eye structure. - Shiho Hayakawa; Yasuharu Takaku; Jung Shan Hwang; Takeo Horiguchi; Hiroshi Suga; Walter Gehring; Kazuho Ikeo; Takashi Gojobori (PLoS ONE, 2015)
The ocelloid is an extraordinary eyespot organelle found only in the dinoflagellate family Warnowiaceae. It contains retina- and lens-like structures called the retinal body and the hyalosome. The ocelloid has been an evolutionary enigma because of its remarkable resemblance to the multicellular camera-type eye. To determine if the ocelloid is functionally photoreceptive, we investigated the warnowiid dinoflagellate Erythropsidinium. Here, we show that the morphology of the retinal body changed depending on different illumination conditions and the hyalosome manifests the refractile nature. Identifying a rhodopsin gene fragment in Erythropsidinium ESTs that is expressed in the retinal body by in situ hybridization, we also show that ocelloids are actually light sensitive photoreceptors. The rhodopsin gene identified is most closely related to bacterial rhodopsins. Taken together, we suggest that the ocelloid is an intracellular camera-type eye, which might be originated from endosymbiotic origin.